2002
DOI: 10.1002/1099-0690(200212)2002:23<4011::aid-ejoc4011>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Nitrogen Monoxide (Nitric Oxide) in the Nitration of a Tyrosine Derivative and Model Compounds

Abstract: The nitration of tyrosine derivatives with nitrogen monoxide (nitric oxide) occurs only in the presence of dioxygen, and the hypothesized mechanism involves nitrogen dioxide (·NO2). For better understanding of the reaction mechanism, the nitration of model compounds − such as 1‐ and 2‐naphthols and their corresponding 2‐ and 1‐nitroso derivatives − with nitrogen monoxide in the presence and in the absence of dioxygen was studied. The results described here show that tyrosine and naphthols do not undergo nitros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Other studies performed recently by our group on the interaction of nitric oxide with naphthols in the presence or absence of oxygen, showed that there is no reaction when oxygen is absent, whereas in its presence, high yields of nitronaphthols are obtained. 20 In addition, the results obtained are interesting from the antioxidant perspective of these indolinonic aminoxyls. Several studies have now highlighted the excellent…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies performed recently by our group on the interaction of nitric oxide with naphthols in the presence or absence of oxygen, showed that there is no reaction when oxygen is absent, whereas in its presence, high yields of nitronaphthols are obtained. 20 In addition, the results obtained are interesting from the antioxidant perspective of these indolinonic aminoxyls. Several studies have now highlighted the excellent…”
Section: Discussionmentioning
confidence: 93%
“…int.) 372 (M ϩ , 2), 342 (100), 326 (20), 266 (89); HRMS calcd. for C 21 H 16 N 4 O 3 372.1222, found 372.1215.…”
Section: -Methyl-2-phenyl-3-phenylimino-5-nitro-n-nitrosoindoline (4c)mentioning
confidence: 99%
“…While several diastereoselective oxygen radical cyclizations have been developed for the synthesis of optically active cyclic ethers, few enantioselective methods have been reported. In biological system, oxidative dimerization of phenolic substrates is known to proceed with complete enantioselectivity 35. Significantly, Ferringa and Wynberg for the first time achieved a bioinspired oxygen radical cyclization of phenol derivatives using a stoichiometric quantity of chiral copper‐diamine complexes, albeit with low enantioselectivity (∼1.3% ee) 32c.…”
Section: Enantioselective Aerobic Oxidative Oxygen Radical Cyclizationmentioning
confidence: 99%
“…For well over a century, the oxidation of sterically hindered phenols by nitrogen oxide free radicals has been explored 3. Although the literature results for NO · are conflicting,2d,3f it is clear that nitrogen dioxide (NO 2 · ) quickly oxidizes phenols 3c3f…”
Section: Introductionmentioning
confidence: 99%